PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP KINERJA BENDAHARA DESA (Studi Kasus Pada Desa Di Kabupaten Pinrang) - Triseptya, Ghaliyah Nimassita; Hatta, Harmiati (Jurnal Ilmiah Ecosystem, 2018)
The current performance conditions of local government officials and treasurers are still low, especially the ability to manage regional finances, especially in rural areas. The Ministry of Finance also provides the same assessment of the village apparatus that has not yet shown its readiness for the receipt of village funds. The training seeks to provide intense learning about the importance of having the competencies needed to complete the work. An employee who has good knowledge, skills, abilities, and work attitude will always be motivated to work effectively, efficiently and productively in accordance with the position he holds. The purpose of this study is to analyze the influence of training on village treasurer performance and competence towards village treasurer performance The sample in this study is treasurer as village fund manager in Pinrang district. This study uses a quantitative approach and the data analysis used is multiple linear regression. The results showed that there was a positive influence between training on the performance of the village treasurer indicating that the higher / more frequent training, the more it would improve the performance of the village treasurer. The positive influence between competency on the performance of the village treasurer shows that the higher the competence, the more it will improve the performance of the village treasurer.